Respuesta :
Step 1: Simplify both sides of the equation.
5(−4a+8)−5(6a−5)=15
(5)(−4a)+(5)(8)+(−5)(6a)+(−5)(−5)=15
−20a+40+−30a+25=15
(−20a+−30a)+(40+25)=15
−50a+65=15
−50a+65=15
Step 2: Subtract 65 from both sides.
−50a+65−65=15−65
−50a=−50
Step 3: Divide both sides by -50.
-50a/-50=-50/-50
Therefore, the answer would be a=1.
We can factor 5 at the left hand side:
[tex]5[(-4a+8)-(6a-5)]=15[/tex]
Divide both sides by 5:
[tex](-4a+8)-(6a-5)=3 \iff -4a+8-6a+5 = 3[/tex]
Sum like terms:
[tex]-10a+13=3[/tex]
Subtract 13 from both sides:
[tex]-10a=-10[/tex]
Divide both sides by -10:
[tex]a=1[/tex]